(untitled) (Medical Forum Monthly, 2020)
Objective: This study was planned to estimate the possible risk factor of burn wound infection, frequency and antibiotic resistant to pseudomonas aeruginosa in burn patients. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Microbiology Bolan Medical Complex Hospital Quetta from November 2018 to November 2019. Materials and Methods: A total of 270 Swab samples were collected from 137 burn wound infected patients from BMC Hospital Quetta. Samples were then subjected to culture on different microbiological media along with Gram staining different biochemical tests and antimicrobial sensitivity was done with disc diffusion procedure. Results: Revealed 220 out of 270 (81.48%) sample were contaminated with in different microorganism. Out of these positive culture n=125 (57%) strains of pseudomonas aeruginosa were isolated. The most common cause was flame burns n=57(41.59 %), followed by scalds burns 38 (27.72 %), electric burns 23 (16.77 %) and chemical burns 19 (13.87 %), respectively. A total 125 isolates of Pseudomonas aeruginosa were recovered from burn patients and the most resistance 100% antibiotic was ampicillin and doxicillin. And least resistant of drugs are azithromycin and imipenem. Conclusion: Increased trend of antimicrobial resistance is an alarming in infections in the area. Moreover, majority of burn patients were male aging above 20 years with flame burn the main cause of accident and incident.